1998
DOI: 10.1063/1.477146
|View full text |Cite
|
Sign up to set email alerts
|

A spectroscopic study of CaOCH3 using the pump/probe microwave and the molecular beam/optical Stark techniques

Abstract: The Stark effect on the R (0,0.5) ( = 17682.9251 cm ) and P (0,1.5) ( = 17682.1966 cm ) branch features of the (0,0) band system of calcium methoxide, CaOCH , was measured and analyzed to give the permanent electronic dipole moments, , of 1.58(8)D and 1.21(5)D for the and states, respectively. The dipole moments are compared with other monovalent calcium compounds and those predicted from a simple electrostatic model. Pure rotational transitions in the state were recorded using the pump/probe microwave-optica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
27
0

Year Published

2002
2002
2016
2016

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 30 publications
(28 citation statements)
references
References 37 publications
1
27
0
Order By: Relevance
“…We removed the ground-state distortion coefficient D K which previously had been fixed [1] at a value determined with microwave accuracy for CaOCH 3 [6], and whose contribution to all line wavenumbers was less than the experimental uncertainty.…”
Section: Spectra and Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…We removed the ground-state distortion coefficient D K which previously had been fixed [1] at a value determined with microwave accuracy for CaOCH 3 [6], and whose contribution to all line wavenumbers was less than the experimental uncertainty.…”
Section: Spectra and Analysismentioning
confidence: 99%
“…In the first iteration, the data for each isotopomer were fitted to the same set of upper-state parameters considered in our first paper [1]. The ground-state constants for the main isotopomer CaO 12 CH 3 were fixed at the values used in our original study [1], which had been obtained with microwave accuracy [6]. All other parameters were optimized, and the results examined for isotopic consistency.…”
Section: Spectra and Analysismentioning
confidence: 99%
“…A standard nonlinear least-squares optimization procedure (Levenberg-Marquardt) was used to fit the data. We initially assigned three subbands with K = 0, ±1 and, fixing the ground state constants to those of Namiki et al (12), fitted the data to derive an initial set of upper state constants. These were then used to create a synthetic spectrum as described below and to calculate line positions for additional values of K .…”
Section: Least-squares Analysis and Spectral Simulationsmentioning
confidence: 99%
“…Calcium species have drawn particular attention: CaOH should be abundant in circumstellar envelopes (7) and the question of its electric dipole moment has been the subject of both experimental (8) and theoretical (9) investigations. Marked similarities between spectra of linear CaOH and the Ca monohalides invited extension of these studies to CaR compounds of lower symmetries, in order to understand their electronic structure and bonding: for instance CaNH 2 (10) for C 2v , CaCH 3 (11) and CaOCH 3 (12,13) for C 3v . The C 3v species are of particular interest for Jahn-Teller studies, as shown in a recent review (14), because they give access to degenerate E electronic states where such vibronic interaction can take place.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation